2022
DOI: 10.1093/ageing/afac286
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions in older adults with cognitive frailty: a systematic review and meta-analysis of randomised controlled trials

Abstract: Background interventions targeting older adults with cognitive frailty have grown rapidly in recent years with inconsistent findings. However, there is no meta-analysis that has synthesised pooled estimates. Objective to synthesise the pooled effect of current targeted interventions in older people with cognitive frailty. Methods we conducted a systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
2
2
1
Order By: Relevance
“…The prevalence rates of MCI, PF, and CF among the sample population were approximately 12%, 15%, and 11% respectively. Compared with previous studies, the prevalence rate in this study was lower for MCI and somewhat higher for PF and approximately equal for CF (Kim et al, 2019; Shimada et al, 2013; Xie et al, 2021; Zheng et al, 2022). A systematic review reported that the CF prevalence among older adults varied widely from 1% to 22.6% across studies due to variations in operational definitions of CF (Zheng et al, 2022).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The prevalence rates of MCI, PF, and CF among the sample population were approximately 12%, 15%, and 11% respectively. Compared with previous studies, the prevalence rate in this study was lower for MCI and somewhat higher for PF and approximately equal for CF (Kim et al, 2019; Shimada et al, 2013; Xie et al, 2021; Zheng et al, 2022). A systematic review reported that the CF prevalence among older adults varied widely from 1% to 22.6% across studies due to variations in operational definitions of CF (Zheng et al, 2022).…”
Section: Discussioncontrasting
confidence: 85%
“…Compared with previous studies, the prevalence rate in this study was lower for MCI and somewhat higher for PF and approximately equal for CF (Kim et al, 2019; Shimada et al, 2013; Xie et al, 2021; Zheng et al, 2022). A systematic review reported that the CF prevalence among older adults varied widely from 1% to 22.6% across studies due to variations in operational definitions of CF (Zheng et al, 2022). As the ageing population continues to accelerate, the number of older adults with CF will increase substantially due to age‐related biologic changes.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…V současné době výrazně častěji využívané materiály při tarzofrontálním závěsu jsou ale zejména již zmíněná autogenní nebo alogenní fascia lata femoris [117][118][119] a syntetické materiály jako silikon, Gore-Tex nebo polypropylen [119][120][121].…”
Section: Okuloplastická Chirurgieunclassified
“…For instance, a network meta-analysis on the effect of exercise to improve cognition in older adults indicated that resistance training (RT) appears to have larger beneficial effects on cognitive and motor functioning than other exercise modalities, although more research has been done on aerobic exercise training [10]. In general, the beneficial effect of exercise was found for all subcognitive domains, with resistance exercise having the greatest benefits on executive function, according to a meta-analysis [11]. Another meta-analysis in individuals with MCI showed that RT improved cognition and alleviated MCI [12].…”
Section: Introductionmentioning
confidence: 99%